COACHING CLINIC BOLA VOLI BAGI GURU PENDIDIKAN JASMANI DI KECAMATAN TAJUR HALANG, BOGOR - Tirto Apriyanto (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
AbstractThe limitations of the curriculum and basic education regarding the ramifications of the physical  education teacher mean that students only have limited opportunities to move and train as well. The  energy possessed by students in their growing age demands a positive and directed channel. Therefore the  ability of existing teachers requires additional guidance and insight to enrich experiences and innovations  in fostering students in their schools. Global Insani School is an Islamic religion-based school located in  the Tajur Halang District and has its own buildings and facilities independently. The location is in a  developing area between residential areas. We have made this school with adequate facilities as partners  for coaching clinic activities as well as being a promotional event for physical education teachers in the  vicinity to inform their students. This activity is in order to make a fundamental contribution to the physical education teacher as a target.  This training provides insight, knowledge and direct drill for physical education teachers about the theory  and practice of volleyball, as well as provisions and opportunities in order to participate in building  student activities in a positive and directed way through volleyball learning. The resulting output is in the  form of teacher competence in fostering volleyball in each school, and their environment. This activity  also had an impact on volleyball activities in schools and the community in order to participate in the  championship (video contest) which was held 2 months after the coaching clinic. AbstrakKeterbatasan kurikulum dan pendidikan dasar tentang kecabangan dari guru pendidikan jasmani  menjadikan siswa hanya mendapatkan peluang bergerak dan berlatih yang terbatas pula. Energi yang  dimiliki para siswa dalam usia pertumbuhan sangat menuntut penyaluran yang positif dan terarah. Oleh  karena itu kemampuan guru yang ada membutuhkan bimbingan dan tambahan wawasan guna  memperkaya pengalaman dan inovasi dalam membina siswa di sekolahnya. Sekolah Global Insani  adalah sekolah berbasis agama Islam yang berada di Kecamatan Tajur Halang dan memimilki gedung  dan fasilitas sendiri secara swadana. Lokasinya berada di wilayah yang sedang berkembang diantara  pemukiman penduduk. Sekolah dengan fasilitas cukup memadai ini kami jadikan mitra untuk kegiatan  coaching clinic sekaligus dapat menjadi ajang promosi bagi guru pendidikan jasmani di sekitarnya untuk  menginformasikan kepada siswanya. Kegiatan ini dalam rangka memberikan kontribusi mendasar pada guru pendidikan jasmani sebagai  sasaran. Pelatihan ini memberikan wawasan, pengetahuan dan drill langsung terhadap guru-guru  pendidikan jasmani tentang teori dan praktek permainan bola voli, sekaligus bekal dan peluang dalam  rangka berpartisipasi membangun aktifitas siswanya dengan hal positif dan terarah melalui  pembelajaran permainan bola voli. Hasil luaran yang dihasil berupa kompetensi guru dalam membina  cabang olahraga bola voli di masing-masing sekolah, dan lingkungannya. Kegiatan ini juga berdampak dampak terhadap kegiatan bola voli di sekolah dan masyarakat dalam rangka mengikuti kejuaraan  (video kontes) yang diselenggarakan 2 bulan setelah kegiatan coaching clinic.